Soft Contact Lenses and Solutions in Canada - Inns, H.D.E (Canadian Journal of Optometry, 1980)
Factual background information is provided on hydrophylic lens polymers and the changes in lens parameters when a change is made in the temperature, tonicity or pH of the solution they are immersed in. Cleaning and disinfection are discussed under three headings. 1) Cleaning: a) surfactants b) oxidizing agents c)enzyme cleaners; 2) Heat disinfection; 3) Chemical disinfection: a) antimicrobial substances b) oxidative substances. Tables list details of the available lenses, the systems, the salines, the surfactants, the chemical disinfectants, the extra cleaners and the ocular lubricants.